2009
DOI: 10.1177/0018720809340341
|View full text |Cite
|
Sign up to set email alerts
|

Can Metric Feedback Training Hinder Actions Involving Distance?

Abstract: Distance estimation training with metric feedback may not generalize to other tasks and may even degrade performance on certain tasks. Future research must specify the conditions under which distance estimation training with metric feedback leads to performance improvements and decrements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 49 publications
(114 reference statements)
3
24
0
Order By: Relevance
“…More specifically, we predicted that what was essentially our original transfer task (i.e., throwing) would affect subsequent throwing, but would not affect what was essentially our original training task (i.e., metric distance estimation). The results of the present study confirmed our predictions, which supported our argument that the negative transfer that we reported in Jones et al (2009) stemmed from cognitive intrusion. To be clear, we do not claim that the negative transfer across settings that was reported in Ferris (1972Ferris ( , 1973a also stemmed from cognitive intrusion.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…More specifically, we predicted that what was essentially our original transfer task (i.e., throwing) would affect subsequent throwing, but would not affect what was essentially our original training task (i.e., metric distance estimation). The results of the present study confirmed our predictions, which supported our argument that the negative transfer that we reported in Jones et al (2009) stemmed from cognitive intrusion. To be clear, we do not claim that the negative transfer across settings that was reported in Ferris (1972Ferris ( , 1973a also stemmed from cognitive intrusion.…”
Section: Discussionsupporting
confidence: 92%
“…In summary, the results of the present study supported our argument that the negative transfer across tasks that we reported in Jones et al (2009) estimation training to distance estimation tasks that are primarily perceptual-motor in nature. Furthermore, our results suggest that researchers must develop a better understanding of distance estimation tasks and settings, as well as how metric estimation training transfers to those tasks and settings.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations